Childhood Grave’s-an experience from a tertiary care center - Vikrant Ghatnatti,; Nilakshi Deka,; Neeta PN, (Asian Journal of Medical Sciences, 2023)
Background: Graves’ disease (GD) attributes for important cause for childhood hyperthyroidism with a prevalence of 0.02%. Initial treatment for GD is the use of antithyroid drugs (ATDs), which is well accepted. The remission rate is around about 30% of children treated with ATD. Aims and Objective: (1) To assess the predictors of relapse and remission after ATD in children with Grave’s disease. (2) To study the clinical profile at presentation and treatment outcome of children with Grave’s disease. Materials and Methods: We conducted a prospective cohort study of children diagnosed for GD (n=27) and treated with either carbimazole (0.6–0.8 mg/kg), methimazole (0.2–1 mg/kg), or (propylthiouracil, 5–10 mg/kg) and continued till euthyroid state was achieved. The dose was titrated every 2 months once till the achievement of the euthyroid state. Assessment of remission and relapse was done within a year of stopping the drug. Results: The overall estimated relapse rate for hyperthyroidism was 54.1% (13 patients), within a year of stopping ATD with a mean duration treatment of 24.23±7.44 months. Multivariate survival analysis showed that the risk of relapse (87.5%) was higher for patients of a body mass index SD score <0.5 and a large goiter. Pre-pubertal patients had higher relapse rate than pubertal patients (OR- 3.24, P=0.04). No other clinical variables such as age, gender, and Wayne Index were significantly associated with relapse, though patients in the relapse group were younger, and had a male predominance with higher Wayne index scores. Conclusion: GD in children has a high relapse rate. Severity of the disease as measured by various clinical methods is important in predicting relapse.